Usefulness of 18F-FDG PET Associated With a High-Fat, Low-Carbohydrate Preparation for the Detection of a Myocardial-Embedded Metastasis. (May 2017) - Djaileb, Loïc; Mandry, Damien; Riou, Laurent; Marie, Pierre-Yves; Verger, Antoine
Abstract : Abstract: The detection of left ventricle metastases is highly relevant because of the risk of severe adverse outcomes such as ventricular arrhythmia. We report herein the case of a 68-year-old man who presented with a ventricular tachycardia due to a myocardial metastasis from a renal cell carcinoma. The metastasis was embedded within the left ventricular lateral wall. It was identified on the basis of persistent 18 F-FDG focal uptake following the ingestion of a high-fat, low-carbohydrate preparation.